What general practitioners said about the palliative care case conference in residential aged care: An Australian perspective. Part 1. (April 2014) - Tuckett, Anthony; Parker, Deborah; Clifton, Karen; Glaetzer, Karen; Greeve, Kim; Israel, Fiona; Jenkin, Peter; Prior, Teresa; Reymond, Elizabeth; Walker, Helen
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To examine the views of general practitioners on providing a palliative approach in residential aged care and in particular their experiences with the palliative care case conference. Background The national project sought to implement and evaluate a comprehensive evidence-based palliative approach in residential aged care. Methods A purposive sample of 11 general practitioners (GPs) across Western Australia (2), South Australia (6), and Queensland (3) participated in face-to-face, semi-structured interviews. Qualitative content analysis was used to generate the core categories. Results The evaluation by the GPs of the palliative care case conference in residential aged care is explained through three core themes: people, place, and performance. Understanding what GPs say about the people involved and the place in which they work, namely the residential aged care facility, can purposefully inform practice and policy. What GPs say about the performance or 'doing' a palliative care case conference is provided in Part II of this two part series. Conclusion The views of GPs, on providing a palliative approach in residential aged care facilitates, offer a critical reflection on current practices and systems.